CONTROLLING THE OPERATION OF THE REMOTE DEVICEUSING FLASK PYTHON SERVER - CHYHIN, Vasyl; PAZYNIUK, Mykhailo; TERENDII, Olha; MENSHIKOV, Oleksii (Herald of Khmelnytskyi National University. Technical sciences, 2023)
A computer model of controlling an unmanned aerial vehicle (UAV) using remote cloud technologies according to predetermined scenarios from the user’s desktop was studied. For this, an experimental setup was created, which includes an unmanned aerial vehicle of the quadcopter type, a personal computer with the Windows operating system, a Raspberry Pi 3 on-board computer with the Raspbian Linux operating system, a Pi Camera V2 video camera, and a Pixhawk autopilot. Worked out connection sequence between client (web browser user) and server (Raspberry Pi 3 with Flask system) and execution of remote commands using HTTP requests. As a framework, the Flask system was chosen, which is one of the simplest and has comprehensive, small-volume documentation. According to the obtained research results, a model of controlling the UAV from the desktop of the user’s personal computer through the on-board computer without using a standard control panel and operator is proposed. According to the obtained research results, a model of remote control of an unmanned aerial vehicle with an on-board computer of the Raspberry Pi type using remote cloud technologies and a control program according to predetermined scenarios is proposed. At the same time, the user works only with the desktop of a personal computer, and accesses through an external or internal network and a Flask-type server to the on-board computer of the UAV without using a standard control panel and operator. The proposed experimental setup includes an unmanned aerial vehicle of the quadcopter type with a Q450 frame and D2212-920 kv engines, a personal computer with a Windows operating system, a Raspberry Pi 3 on-board computer with a Raspbian Linux operating system. It made it possible to realize the set goal of researching the process of controlling an unmanned aerial vehicle using a Flask-type server. It was found that the full time of passing the HTTP request through the browser window and receiving a response from the server about the successful completion of the task does not exceed one second. In the future, it is planned to work out more complex processes of launching and controlling an unmanned aerial vehicle in flights according to predetermined scenarios, including the performance of a task such as neutralizing unauthorized aerial vehicles, as well as returning one’s own UAV to the place of deployment. The proposed system of remote control with the Flask server can also be useful for receiving an immediate notification when detecting certain sounds from foreign unmanned aerial vehicles, detecting and measuring their flight parameters.